Design and Analysis of Heavy-Duty Vehicle Chassis - Sahil Singan; Girish Muneshwar; Aditya Deshmukh; Kartik Nipane; Prajwal Veer (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Automotive Chassis is the main body of a vehicle which act as a frame work for supporting the other part of vehicle. It should work on various parameter like shock, twist, vibration etc. it should have adequate bending stiffness for better handling characteristics. Stress and equilateral stress are basic characteristics for designing of a firm chassis. There are many industrialized sectors using truck as means of transportation for logistics, agricultures, factories and other industries. In this paper, three different material was adopted on the C-section truck frame design. ASTM A302, HSS 550 and ASTM A710 were structurally analysed on the heavy truck frame through finite element analysis. The results were compared and the best truck chassis material was identified with lower stress and deflection.